Demanding good governance : lessons from social accountability initiatives in Africa - McNeil, Mary; Malena, Carmen; World Bank. (Washington, D.C. : World Bank, 2010)
The book contains case studies from cross sections of countries drawing on initiatives launched and implemented by civil society groups and by local and national governments in countries with a wide range of political contexts and cultures. It explains what social accountability means in the African context distilling some common success factors.
Includes bibliographical references and index.
oif 27/03/14, ijb 20/02/2019
Loan
Keywords: Social accounting